2023
DOI: 10.1161/circresaha.123.321563
|View full text |Cite
|
Sign up to set email alerts
|

HDL Function and Atherosclerosis: Reactive Dicarbonyls as Promising Targets of Therapy

Abstract: Epidemiologic studies detected an inverse relationship between HDL (high-density lipoprotein) cholesterol (HDL-C) levels and atherosclerotic cardiovascular disease (ASCVD), identifying HDL-C as a major risk factor for ASCVD and suggesting atheroprotective functions of HDL. However, the role of HDL-C as a mediator of risk for ASCVD has been called into question by the failure of HDL-C–raising drugs to reduce cardiovascular events in clinical trials. Progress in understanding the heterogeneous nature of HDL part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 256 publications
0
9
0
Order By: Relevance
“…Inflammatory plaque cells release factors that attract extra immune cells and suppress their excretion, thus leading to a chronic inflammatory condition and plaque development. 8,9 Bigger plaques (stenosis >70%) that block the bloodstream eventually cause symptoms such as angina or lameness, which become chronic. Nevertheless, inflammatory plaque cells also secrete matrix metalloproteinases capable of destroying the fibrous membrane and ultimately stimulate plaque rupture, acute ischemia, and thrombosis, which are well-known as the key reason for most MIs and strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory plaque cells release factors that attract extra immune cells and suppress their excretion, thus leading to a chronic inflammatory condition and plaque development. 8,9 Bigger plaques (stenosis >70%) that block the bloodstream eventually cause symptoms such as angina or lameness, which become chronic. Nevertheless, inflammatory plaque cells also secrete matrix metalloproteinases capable of destroying the fibrous membrane and ultimately stimulate plaque rupture, acute ischemia, and thrombosis, which are well-known as the key reason for most MIs and strokes.…”
Section: Introductionmentioning
confidence: 99%
“…High-density lipoprotein plays a crucial role in inhibiting inflammatory signaling within macrophages and other cells. However, in patients, oxidative modifications can impair the functionality of high-density lipoprotein, leading to a pro-inflammatory state [ 28 ]. In line with these previous findings, our study demonstrated a significant correlation between MHR and QFR ≤ 0.80, indicating its potential as a relevant marker.…”
Section: Discussionmentioning
confidence: 99%
“…HDL-C is considered the “good” cholesterol. Pharmacoepidemiological studies have shown that HDL-C levels are inversely associated with the incidence of CVD [ 7 , 46 ]. For a long time, the prevention and treatment of AS by increasing HDL-C has been considered to have broad prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have identified an inverse correlation between HDL levels and AS [ 7 , 8 ]. HDL is protective because it removes excess cholesterol from surrounding tissues by reverse cholesterol transport (RCT) and transporting it to the liver for bile excretion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%